Motivations for firearm possession and storage practices among urban young adults: differences between parents and non-parents - Sokol, Rebeccah Lyn (Inj Prev, 2020)
OBJECTIVES: To evaluate motivations for firearm possession among urban young adults and determine if differences emerge between parents and non-parents, and to identify if storage practices differed according to motivation for firearm possession and parenting status. METHODS: We used cross-sectional data among young adults seeking urban emergency department treatment at Hurley Medical Center between 2017 and 2018. Our analyses, completed in 2020, included 194 firearm-possessing young adults, 95 of whom were young parents. RESULTS: Firearm-possessing parents were more likely to have a firearm for protection, than for any other motivation, compared with firearm-possessing non-parents (OR: 2.38, 95% CI 1.06 to 5.46). A significant interaction between parenting status and motivation for possession indicated the association between protective motivations and locked storage was significantly different between parents and non-parents, whereby there was a decreased odds of locked storage among non-parents who were motivated to possess a firearm for protection compared with any other motivation, but this association did not exist for parents (interaction OR=10.57, p<0.05). CONCLUSION: Parental motivation for possessing a firearm most often lies in the desire to protect families. This motivation, however, does not necessitate unsafe storage.